STUDI TENTANG KOMPETENSI PRODUKSI DAN PROMOSI PEMBUAT FILM INDEPENDEN DI SURAKARTA - Rahman, Anung (Seni Media Rekam ISI Surakarta, 2009)
This research is aimed to observe and to analyze carefully the production compe-tence and promotion ability of the indie filmmaker in Surakarta. The research is carried out at indie film community in Surakarta, that consist of academic and general background. The method of the research is qualitative des-criptive. The sampling technique is carried out purposively. The data collection is taken place by interview, observation, and documentary analyzing. The results of the research concludes that the production competence and promo-tion ability of the indie filmmaker from general background is strong. But their tracks of promotion mostly on job for right now. In other side, the production competence and promotion ability of the indie filmmaker from academic back-ground is still weak. Because of those weakness, the potential spectators appreciation are still low than other town. And the other effect, people in Surakarta mostly don’t know about the growing indie phenomenon.Keyword : the indie filmmaker’s, the production competence and promotion abi-lity, spectators appreciation.